2021
DOI: 10.1177/1521025120985228
|View full text |Cite
|
Sign up to set email alerts
|

Student Retention in Higher Education: Why Students Choose to Remain at University

Abstract: This research captured the voices of 578 current university students investigating whether they have considered leaving university without completing their studies, what caused them to consider leaving their studies, and explored the reasons that led them to stay. The majority of participants had considered leaving university without completing their course. Multiple factors contributed to this consideration, with family commitments, financial strain, time management, expected study load, and work commitments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…The sudden shift to virtual teaching and learning impeded the formation of typical student-educator relationships, which, according to Tice et al (2021), created a barrier to developing a sense of belonging. Similar to other findings (Nieuwoudt & Pedler, 2021), some participants in this current study reported that educators positively impacted them, whereas others were affected negatively. Some participants found it challenging to form relationships with educators due to the lack of in-person social interactions.…”
Section: Discussionsupporting
confidence: 90%
“…The sudden shift to virtual teaching and learning impeded the formation of typical student-educator relationships, which, according to Tice et al (2021), created a barrier to developing a sense of belonging. Similar to other findings (Nieuwoudt & Pedler, 2021), some participants in this current study reported that educators positively impacted them, whereas others were affected negatively. Some participants found it challenging to form relationships with educators due to the lack of in-person social interactions.…”
Section: Discussionsupporting
confidence: 90%
“…Students have diverse reasons for withdrawing from higher education, which may include lack of readiness for participation in higher education; lack of academic attainment; the inability to pay tuition fees and living costs; dissatisfaction with the student experience; and the failure to achieve a sense of belonging at the institution, perhaps resulting from the lack of social and/or organizational identification (Barefoot, 2004). Students typically leave a university for a number of reasons, and not just for a single reason (Nieuwoudt and Pedler, 2021). There is consensus in the literature that there is a strong and positive relationship between student satisfaction and student retention (Annamdevula and Bellamkonda, 2016).…”
Section: Retention Of Students In Higher Educationmentioning
confidence: 99%
“…Furthermore, it has an impact on society and the economy through the loss of critical skills and information [22]. There are also financial and reputational implications for institutions, making student retention and success a major concern for universities worldwide [23].…”
Section: Literature Reviewmentioning
confidence: 99%